2015
DOI: 10.1080/02640414.2015.1080384
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary therapy changes superoxide dismutase activity and adiponectin in obese adolescents: a randomised controlled trial

Abstract: The objective of this study is to evaluate the effect of interdisciplinary therapy in the parameters of the oxidative stress and the anti-inflammatory responses of obese adolescents. We selected 57 participants, who were randomly divided into 2 groups: interdisciplinary therapy group and a control group. After 6 months of intervention, 17 participants of the interdisciplinary therapy group and 8 of the control group returned for re-evaluation. The interdisciplinary therapy group participated in a treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
3
12
0
1
Order By: Relevance
“…We found that Zn level was lower in obese subjects, while the level of Cu was higher. Moreover, we found that the level of SOD was decreased in the obese group, indicating Zn and SOD deficiencies in obese subjects, which is line with the previous observation [7,8,28,30,31] .…”
Section: Zinc and Sod Levels In Obese Subjectssupporting
confidence: 92%
“…We found that Zn level was lower in obese subjects, while the level of Cu was higher. Moreover, we found that the level of SOD was decreased in the obese group, indicating Zn and SOD deficiencies in obese subjects, which is line with the previous observation [7,8,28,30,31] .…”
Section: Zinc and Sod Levels In Obese Subjectssupporting
confidence: 92%
“…Finally, 14 RCTs met the inclusion criteria and were included in the meta-analysis. 13, 19, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38 In the included 14 trials, 5 RCTs analyzed leptin, 19, 30, 31, 34, 36 10 analyzed adiponectin, 13, 28, 29, 31, 32, 34, 35, 36, 38 2 analyzed resistin, 31, 36 and only 1 visfatin. 33 …”
Section: Resultsmentioning
confidence: 99%
“…The youths were overweight/obese 28, 29, 31, 33, 34, 37 or obese. 13, 19, 27, 30, 35, 36, 38 Three studies included only boys 28, 32, 37 and three only girls, 33, 34, 35 and the remaining studies included both boys and girls. 13, 19, 27, 29, 30, 31, 36, 38 Participants in three studies were children (6–12 years old), 28, 29, 31 in eight adolescents (13–17 years old), 13, 19, 32, 33, 34, 35, 36, 37, 38 and in the other both age groups were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 3-year longitudinal study, higher concentrations of A-FABP and lower levels of adiponectin were reported as predictors for the development of CVD risk factors [21]. The improvement of adiponectin levels after an exercise-based intervention programme has been associated with improvements in the oxidant status in paediatric populations [68].…”
Section: Blood Vessels and Blood Pressure (Bp)mentioning
confidence: 99%